Effect of Rainfall Intensity on Directional Splash Erosion in Clay Loam Soil under Simulated Condition - Barai, Virendra N.; Satpute, Gajanan U.; Atre, Atul A. (International Journal of Bio-resource and Stress Management, 2018)
An attempt has been made to quantify splash detachment for various combinations of land slopes and rainfall intensities with the help of rainfall simulation system and modified Morgan’s splash cup. The clay loam soil was used to study the splash erosion. Uniformity coefficient of simulated rainfall was above 70% for all the six selected rainfall intensities viz. 7.75, 5.8, 4.23, 3.28, 2.04 and 1.07 cm h-1, which is acceptable. The directional splash soil loss rate (kg ha-1), i.e. upslope and down slope were found increasing with increase in rainfall intensity and land slope. The rate of increase in down slope splash was comparatively more than upslope. The highest soil splash i.e. 17898 kg ha-1 was observed for combination of 10% land slope and 7.75 cm h-1 rainfall intensity in clay loam soil. The results obtained showed that maximum vertical movement of splashed material was 89 cm in clay loam soil, for the combination of rainfall intensity 7.75 cm h-1 and land slope 10%. The maximum horizontal movement of splashed material was found 111.0 cm for the combination of rainfall intensity 7.75 cm h-1 and land slope 10%. The Splashed soil material was spread near about 111.0 cm in the down slope direction and 75.5 cm in the upslope direction which highlights the need to modify the size of splash cup to study the realistic soil movement during splash erosion.